(untitled) (Journal of Hama University, 2020)
The purpose of this study is to find out the teachers’ attitude towards the use of computer as an educational tool. The researcher developed a scale of (30) items to determine teachers’ attitudes , the items of scale were directed to English language teachers (male and female) in secondary schools . Confirmatory and reliability of the scale were conducted. Then , scale were determined to be applied to a sample of (200) male and female English language teachers . The findings suggested that there are no statistically significant differences among English language teachers’ attitudes according to sex variable. The findings also suggested There are statistically significant differences among English language teachers’ attitudes according to scientific qualification variable in favor of doctorate and master degrees then, diploma. The results mainly showed that there are statistically significant differences among English language teachers’ attitudes due to the variable of teaching experience . The researcher suggested that the use of computer for educational purposes should be given greater consideration by developing positive attitudes of English language teachers through providing secondary schools with modern computers and encouraging English teachers by giving them rewards to use modern technology in education .